Public Librarians Hold Critical and Evolving Role as Community Facilitators of Government Information / Zhu, X., Winberry, J., McBee, K., Cowell, E., & Headrick, J. S. (2022). Serving the community with trustworthy government information and data: What can we learn from the public librarians? Public Library Quarterly, 41(6), 574–595. https://doi.org/10.1080/01616846.2021.1994312 - Shen, Lisa (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2023)
Objective – To understand public librarians’ experiences in addressing their communities’ government information and data needs.Design – Semi-structured interviews.Setting – 4 public county library systems in 2 southern states in the United States in early 2019, prior to onset of the COVID-19 pandemicSubjects – 31 public service librarians, recruited through a combination of theoretical and convenience sampling strategies.Methods – The researchers conducted individual interviews, ranging between 30 and 60 minutes, with each participant. Interview recordings were transcribed and processed through the qualitative data software NVivo, using a grounded theory approach with open inductive coding followed by thematic analysis.Main Results – Six major findings were identified through thematic coding, including variability and complexity of reference questions, diversity in patron demographics, need for advanced knowledge of the local community context, preparedness of librarians to provide reference consultation for government information, balance between information and interpretation, and trust issues related to government sources. Challenges related to digital literacy level was a shared factor across multiple themes, as patrons’ government information needs are increasingly impacted by their ability to access web, mobile, and computer technologies, navigate online resources, and interpret bureaucratic vocabulary. Some librarians also expressed their own eroding trust towards the validity of government sources, such as climate change information from the Environmental Protection Agency under the Trump administration.Conclusion – A majority of the findings were consistent with past literature, including the breadth and depth of varying government informational needs of public library patrons and the trust patrons have for their public libraries and librarians. Researchers also noted limited initiatives by public libraries to proactively educate patrons about open data or misinformation and recommended that libraries and library science educators better prepare current and future librarians for their role as government information mediators.